Creativity-focused Technology Education in the Age of Industry 4.0. Issue 2 (2nd April 2020) - Cropley, Arthur
ABSTRACT: Increasing digitization and robotization and the resulting cyber-physical systems (CPSs) are leading to an era in which artificial intelligence (AI) is becoming increasingly prominent in our lives. Making the best use of AI in engineering and technology will require not just practical and technical knowledge and skills but "creatively-focused technology fluency" (CFTF), in order to go beyond algorithmic thinking. The creativity focus involves creativity-facilitating competencies such as managing complexity, thinking critically, envisaging possibilities, tolerating uncertainty, displaying self-efficacy, and communicating skillfully; fostering these is now an important element in technology education. Emphasizing the need for a creativity focus (the "CF" in "CFTF") does not involve neglecting or abolishing traditional knowledge and skills but supplementing them by strengthening creativity-focused competencies.